2014
DOI: 10.5089/9781498377911.001
|View full text |Cite
|
Sign up to set email alerts
|

Credit Quality in Developing Economies: Remittances to the Rescue?

Abstract: This paper analyzes the link between remittances inflows and nonperforming loans (NPLs) in a large sample of developing countries. Theoretical transmission channels include risk coping, exchange rate and growth impacts. Panel data estimates uncover the significant role of remittance inflows in reducing the size of NPLs in recipient economies. Econometric results also indicate a stronger marginal impact of remittances in a context of high macroeconomic instability, suggesting a significant effect of remittances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…Based on these results, an increase in the remittancesto-GDP ratio for CAPDR by 1 percentage point would cause a drop in the NPL ratio by almost 0.5 percentage points. The magnitude of the latter effect is similar to that found by Ebeke et al (2014). Sufficient observations were not available for the Caribbean.…”
Section: The Positive Impact Of Remittances For Financial Sector Devesupporting
confidence: 80%
“…Based on these results, an increase in the remittancesto-GDP ratio for CAPDR by 1 percentage point would cause a drop in the NPL ratio by almost 0.5 percentage points. The magnitude of the latter effect is similar to that found by Ebeke et al (2014). Sufficient observations were not available for the Caribbean.…”
Section: The Positive Impact Of Remittances For Financial Sector Devesupporting
confidence: 80%
“…The GMM estimation technique indicated that the exchange rate, the private credit to GDP ratio and one period lagged NPLs were positively related to NPLs whereas, real GDP growth and the domestic stock price index had a negative impact on NPLs. Ebeke and Loko (2014) investigate the impact of remittances on NPLs for 141 developing countries from 2000 to 2011. The country sample included low-income and middle-income countries.…”
Section: Npls and Its Impact On Banksmentioning
confidence: 99%
“…But this Financial Intermediation has greatly been influenced by remittances from foreign countries. Therefore, remittances can be expected to pave the way for a sound development of a formal financial sector, critical for sustaining high economic growth, Ebeke et al [2]. However, Singer [3] believed that remit-tances tend to be stable and increase during periods of economic downturns.…”
Section: Background Of the Studymentioning
confidence: 99%